The silence of the lambs - Shore, Howard 1946- (The Criterion Collection, 1998)
Commentary by Jonathan Demme, stars Jodie Foster and Anthony Hopkins, screenwriter Ted Tally, and FBI agent John Douglas. Seven deleted scenes. Film-to-storyboard comparison. Storyboards. FBI crime classification manual. Voices of Death: word-for-word statements of convicted serial killers. ; en
Orig.: USA 1990
Keywords: Fiktionale Darstellung; Film